Meeting with Pol Pot [videorecording (DVD)] - Rithy Panh; Guillaume, Pierre Erwan; Jacob, Irène; Colin, Grégoire; Guei, Cyril; Becker, Elizabeth (Journalist) (Strand Releasing, 2025)
Three French journalists travel to Cambodia in 1978 after receiving an invitation from the Khmer Rouge regime, embarking on a perilous adventure.